استقلالية قاضي التحقيق في المملكة العربية السعودية: دراسة تحليليَّة نقديَّة على ضوء الشريعة الإسلامية والقانون الدولي - قرشي، ياسر بن سليم بن سالم (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2018)
The judiciary is regarded as a body that protects the rights and freedoms of individuals from any abuse or tyranny; and that its independence guarantees its power of intervention and influence. Thus, it needs some level of security to ensure the protection of judicature which leads to the independence of judge. Therefore, this research aims at revealing the independence of the investigating judge in the Saudi law, and the security that his independence requires. The problem of research was reflected in the extent to which Saudi law guarantees the independence of investigating judges. The importance of the paper lies in the assessment of this security, the extent of their agreement with Islamic and international laws. The researcher adopts the comparative descriptive analytical approach to collect data. The results of the study confirmed the existence of some problems which hinder the independence of investigating judge in the Saudi law. The researcher recommended some amendments to the legislation to guarantee the independence of investigating judge in the Saudi law.